Risk, Stretch, or Die - Heyden, Saskia (Europa-Universität Viadrina, 2007)
Verzio FF Submission French Drag King Océan LeRoy has been a celebrity in Berlin’s transgender scene for years. Famous for his performances of quick transition from woman to man, Océan also lives a double life: a seductive Drag Star at night, a skilled businesswoman during the day. Parallel lives in contemporary Europe.